Yeast and its uses. - Jana KOPECKÁ; Dagmar MATOULKOVÁ; Miroslav NĚMEC (Kvasný průmysl, 2012)
Yeasts are eukaryotic heterotrophic organisms belonging to fungi. In contrast to other eukaryotes yeasts possess thick and rigid cell wall. As a source of carbon and energy yeast can degrade sugars using two metabolic pathways: aerobic respiration and fermentation. Yeasts are used for various processes. The use of the yeast in food industry as baker's yeast, fodder yeast, for the beer, wine and spirit production is of great importance. Modern biotechnologies use yeast for the production of various substances (vitamins, enzymes, antibiotics, amino acids, proteins). It can be genetically modified to gain new and more convenient properties and to produce desired compounds. Being relatively easy to handle (mutant isolation, gene transfer, cultivation) and of known genome, yeast is a suitable model organism for the study of physiological and metabolic processes and genetics of eukaryotes. However, some of the yeast genera belong to pathogens that are hazardous for immunocompromised people.Yeasts are eukaryotic heterotrophic organisms belonging to fungi. In contrast to other eukaryotes yeasts possess thick and rigid cell wall. As a source of carbon and energy yeast can degrade sugars using two metabolic pathways: aerobic respiration and fermentation. Yeasts are used for various processes. The use of the yeast in food industry as baker's yeast, fodder yeast, for the beer, wine and spirit production is of great importance. Modern biotechnologies use yeast for the production of various substances (vitamins, enzymes, antibiotics, amino acids, proteins). It can be genetically modified to gain new and more convenient properties and to produce desired compounds. Being relatively easy to handle (mutant isolation, gene transfer, cultivation) and of known genome, yeast is a suitable model organism for the study of physiological and metabolic processes and genetics of eukaryotes. However, some of the yeast genera belong to pathogens that are hazardous for immunocompromised people.